Innate arthroscopic skills in medical students and variation in learning curves. - Alvand, A; Auplish, S; Gill, H; Rees, J (2011)
BACKGROUND: Technical skill is an essential domain of surgical competence, and arthroscopic surgery requires a particularly challenging subset of technical skills. The innate ability to acquire arthroscopic skills is not fully understood. The aim of this study was to investigate the innate arthroscopic skills and learning curve patterns of medical students. METHODS: Tests of two arthroscopic tasks (one shoulder and one knee task designed to represent core skills required for arthroscopic training) were conducted in a surgical skills laboratory. The performance of twenty medical students with no previous arthroscopic surgery experience was assessed as they performed thirty repetitions of each task. The primary outcome measure for each repetition was success or failure in performing the task. An individual was deemed "competent" at the conclusion of the testing if he or she achieved stabilization of the learning curve (success on all subsequent repetitions) within twenty repetitions of the task. The secondary outcome measures were objective assessments of technical dexterity (time taken to complete the task, total length of the path traveled by the subject's hands, and number of hand movements) measured with use of a validated motion analysis system. RESULTS: The performance on each task varied among the students. Seven students were unable to achieve competence in the shoulder task and four were unable to achieve competence in the knee task. Motion analysis demonstrated that students who achieved task competence had better objective technical dexterity and thus better innate arthroscopic ability. The total path length and the number of hand movements differed significantly between the students who did and did not become competent at the shoulder task (p < 0.05, Mann-Whitney U test). The difference in path length was also significant for students performing the knee task (p < 0.05). CONCLUSIONS: Variation in innate arthroscopic skill exists among future surgeons, with some individuals being unable to achieve competence in basic arthroscopic tasks despite sustained practice.